2010
DOI: 10.1007/s00415-010-5609-1
|View full text |Cite
|
Sign up to set email alerts
|

Progression in ALS is not linear but is curvilinear

Abstract: The aim of the study is to determine the shape of the progression curve in ALS, assess the impact of clinical variables on the rate of progression, and evaluate the association between functional decline and survival. Data were prospectively collected and entered into a clinical database from all patients seen in 2002-2008 at the Centre SLA, Hôpital de la Salpêtrière, Paris. Variables analyzed were demographic and baseline information, the ALS functional rating scale (ALSFRS-R), strength testing (MMT), and sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
90
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(99 citation statements)
references
References 25 publications
8
90
0
1
Order By: Relevance
“…Using the PRO-ACT database allowed for validation of these findings; for example, site of onset has been shown to affect the slope of ALSFRS and overall survival time [33][34][35][36][37][38][39][40][41], with bulbar onset leading to poor prognosis compared with limb onset. Similarly, age of onset was predictive of prognosis (with poorer prognosis for patients with an later disease onset [34][35][36][37][38][39][40][41][42][43][44]). Other factors connected to prognosis in previous reports included body mass index or absolute weight [42,45]; cognitive functioning [46]; level of uric acid [42,47]; and levels of albumin and creatinine [48,49].…”
Section: Understanding Als Clinical Manifestationmentioning
confidence: 98%
See 1 more Smart Citation
“…Using the PRO-ACT database allowed for validation of these findings; for example, site of onset has been shown to affect the slope of ALSFRS and overall survival time [33][34][35][36][37][38][39][40][41], with bulbar onset leading to poor prognosis compared with limb onset. Similarly, age of onset was predictive of prognosis (with poorer prognosis for patients with an later disease onset [34][35][36][37][38][39][40][41][42][43][44]). Other factors connected to prognosis in previous reports included body mass index or absolute weight [42,45]; cognitive functioning [46]; level of uric acid [42,47]; and levels of albumin and creatinine [48,49].…”
Section: Understanding Als Clinical Manifestationmentioning
confidence: 98%
“…Understanding the development of ALSFRS over time is relevant for understanding disease progression. Reports vary regarding the linearity of ALSFRS-R measure over time [34,43,54,55], and these reports likely depend on number of patients, distribution of disease progression, and frequency of measuring ALSFRS-R.…”
Section: Understanding Als Symptom Profilementioning
confidence: 99%
“…This model depicted in the left part of Figure 5 (A) indeed suggested a nonlinear ALSFRS trajectory; however, we found a faster instead of a slower disease progression, as reported earlier (cf. Figure 1 in Gordon et al 2010). The random slope parameters necessary for the definition of the ALSFRS slope between the linear and the quadratic model were highly correlated.…”
Section: Alsfrs Slope Describes Alsfrs Score Trajectorymentioning
confidence: 99%
“…Gordon et al Gordon et al (2010) reported that the mean ALSFRS trajectory over time is nonlinear. We also modelled deviations from a linear ALSFRS trajectory by allowing an additional fixed effect in quadratic time β 2 t 2 in model (2).…”
Section: Alsfrs Slope Describes Alsfrs Score Trajectorymentioning
confidence: 99%
See 1 more Smart Citation